BESTMITTEL AND SILICA FUME EFFECT ON CONCRETE COMPRESSIVE STRENGTH WITH SEAWATER CURING - Tandilino, Frianto; Hutabarat, Lolom Evalita; Simanjuntak, Risma Masniari (Jurnal Pensil : Pendidikan Teknik Sipil, 2024)
The frequency of tidal floods caused by seawater threatens coastal buildings. This study aims to see how using seawater for concrete treatment affects the resulting compressive strength. This study used additives such as Bestmittel to expedite hardening and boost compressive strength, as well as silica fume to increase porosity and prevent concrete from becoming porous owing to chloride ion intrusion from seawater. The findings of concrete compressive strength tests were achieved through laboratory testing using cylindrical test objects measuring 150 mm in diameter and 300 mm in height. The test specimens were ordinary concrete with 0.6% bestmittel and a Silica Fume combination with varying percentages of 15%, 20%, and 25% substituting partial cement. Meanwhile, the concrete treatment employs both fresh water and seawater. Pressure tests were performed at 14 and 28 days. At 14 days, concrete with fresh water treatment and a bestmittel content of 0.6% and silica fume concentrations of 15%, 20%, and 25% have compressive strengths of 25.53 MPa, 27.11 MPa, and 26.04 MPa, respectively. Meanwhile, it was 26.34 MPa, 27.61 MPa, and 26.75 MPa after 28 days of concrete age. At 14 consecutive days of concrete age, concrete with seawater treatment had a reduced compressive strength. 19.66 MPa, 22.13 MPa, and 23.07 MPa, respectively. Meanwhile, at 28 days, the pressures were 20.53 MPa, 24.77 MPa, and 25.53 MPa. Using 6% bestmittel followed by 15-20% SF can boost the strength of the concrete and let it survive reduced compressive strength due to seawater infiltration.